Seleksi Penerima Beasiswa Pada ITB Stikom Bali Dengan Metode Weighted Aggregated Sum Product Assessment - Ulandari, Ni Wayan Ari; Suwirmayanti, Ni Luh Gede Pivin; Putra, I Putu Warma (Jurnal Teknik Informatika UNIKA Santo Thomas, 2023)
ITB STIKOM Bali annually conducts a selection of new student admissions according to the registra-tion calendar, on the registration calendar there is a registration wave where each wave has its own provisions. Currently, ITB STIKOM Bali's new student admissions are held online and it is possible that they will return offline, which will be adjusted to government policy. In addition to the selection of new student admissions, ITB STIKOM Bali also conducts a selection of scholarships for prospective students who cannot afford it. The scholarships given are KIP Lectures or Indonesian Smart Cards (KIP) for Lectures, where the KIP Lecture program is the Government's effort to help students who have economic limitations but have a great desire to study but excel, to continue their studies at public and private universities. . So that the KIP Lecture Scholarship Recipients are right on target and not misdirected, researchers will conduct research on the selection of KIP Lecture scholarship recipients at ITB STIKOM Bali using the WASPAS (Weighted Aggregated Sum Product Assessment) method. Providing KIP scholarships for Studying at ITB STIKOM Bali, a decision support system is needed to provide recommendations to student leaders who are entitled to get scholarships according to catego-ries or conditions. Researchers will use the WASPAS method, where Waspas is a method that can re-duce errors or optimize interpretation for the selection of the highest and lowest values. Based on the explanation above, this research will use the WASPAS method with the research title Selection of Scholarship Recipients at ITB STIKOM Bali with the WASPAS method.